STUDI KOMPARASI MODEL PEMBELAJARAN KOOPERATIF TPS DAN TGT UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMA NEGERI 1 RAMBAH ROKAN HULU - Kristiyanti, Friska Kristiyanti Friska; ', Rasmiwetti Rasmiwetti; ', Susilawati Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is an experimental research with randomized control group pretest-posttest design that was done at first grade students of SMA Negeri 1 Rambah Rokan Hulu. The purpose of research are to know whether the aplication of cooperative learning models TPS and TGT can improve the student’s achievement in Hydrocarbons topic, and whether there are significant differences between the aplication of the TPS and TGT models in improving the student’s achievement. There are three classes which were choiced as the research samples. Xb as the first experiment class (TPS), Xa as the second experiment class (TGT) and Xf as the control class. The three samples were tested for normality using the Liliefors test and for homogenity using the Bartlett test. The analyze of hypotesis is using t-test. Based on the result of data analysis, the cooperative learning models TPS and TGT can improve the student’s achievement (tobserved = 1,96 > ttable = 1,67 ; tobserved = 3,12 > ttable = 1,67). The are no significant differences between the aplication of the TPS and TGT models in improving the student’s achievement (tobserved = 1,78 < ttable = 2,00).Keywords : Comparison Study, Think Pair Square (TPS), Team Games Tournament (TGT), Student’s Achievement, Hydrocarbons.